A gestão de logística sustentável no comando ambiental da Brigada Militar do estado do Rio Grande do Sul - Moreira, Antonio Marcos Silveira (2017)
Sustainability can be seen as human actions, resulting from the interaction of nature, with harmony between the economy, society and the environment, in order to guarantee a preserved environment for the present and future generations. Regarding sustainability in public organizations, as major consumers of goods and services, these should adopt practices aimed at minimizing the social and environmental impacts arising from their activities. The Sustainable Logistics Management Plan, already adopted in some federal institutions, can also be adopted at the state level, since it represents another management tool, allowing a diagnosis of the situation, with objectives, goals, actions, responsibilities, deadlines and indicators , for sustainable practices and rationalization of public administration expenditures and processes. In this context, the objective of the present work is the elaboration of a proposal for a Sustainable Logistics Management Plan - PLS to the Environmental Commander of the Military Brigade - CABM of Rio Grande do Sul, considering the importance of public organizations, through their managers, in take precedence over the achievement of sustainable actions, innovative attitudes and, above all, good practices focused on responsibility towards the environment. It was tried to identify, among some Sustainable Logistics Management Plans, already adopted in federal public institutions, models that allow establishing practices of sustainability and rationalization of resources and processes in the public administration and adaptable to the organization object of this study, a public level institution state. It is a descriptive study, and to obtain the necessary data we used participant observation, documentary analysis and research with internal public, through a questionnaire with open questions, analyzed qualitatively. The results indicate that although the Environmental Brigade of the Military Brigade is an organ focused on the prevention and control of environmental crimes, as in most public organizations at the state level, it lacks planned actions on the subject of sustainability, although isolated actions have been identified. Finally, based on the Sustainable Logistics Management Plans of the Federal University of Santa Maria - UFSM, Federal University of Pampa - UNIPAMPA and the Federal Institute of Education Science and Technology of the South of Minas Gerais - IFSULDEMINAS, a proposal was made for PLS , which includes material for consumption, electric energy, water and sewage, selective collection, purchases and contracting, personnel displacement and quality of life at work.